“É humana a escravidão?”: perguntas, respostas e produção de consenso na gestão da participação em sala de aula contemporânea - Mariano, Lorena Silva (2020)
This research has as objective to investigate and describe the sequential trajectories, that are built by talk-in-interaction in the contemporary classroom, by questions designs (HAYANO, 2013). For this purpose, we attended an elementary public school fro